Collimated γ-flash emission along the target surface irradiated by a laser at non-grazing incidence - M Matys; P Hadjisolomou; R Shaisultanov; P Valenta; M Lamač; T M Jeong; J P Thistlewood; C P Ridgers; A S Pirozhkov; S V Bulanov (New Journal of Physics)
The interaction of a high-power laser with a solid target provides ways to produce beams of γ -photons. For normal incidence of the laser on the target the beams usually appear in a form of two lobes, which are symmetric with respect to the laser propagation axis. In this work we demonstrate via three-dimensional particle-in-cell simulations a regime where for oblique incidence the emission of a collimated γ -photon beam is in the direction parallel to the target surface. The process is ascribed to the interference pattern in the electromagnetic field formed by the incident and reflected laser pulse. The electromagnetic field accelerates electrons to the GeV energy level, while temporarily directing their momentum along the target surface. Consequently, they emit a collimated γ -photon beam in the same direction. The dependencies of γ -photon emission on the incident angle, laser pulse polarization, power and duration and target thickness and preplasma are also addressed in the paper. The beam directionality is important for designing future experiments. In addition, this setup causes the generation of high-order harmonics propagating along the target surface.